2020
DOI: 10.1111/afe.12373
|View full text |Cite
|
Sign up to set email alerts
|

The mating strategy and reproductive performance of Agriphila aeneociliella (Lepidoptera: Crambidae), a new insect pest of wheat in China

Abstract: The Eastern Grass‐veneer Agriphila aeneociliella (Eversmann) (Lepidoptera: Crambidae) is a serious stem‐feeding pest of wheat crops that has become established in China in recent years. A better understanding of the mating strategy and reproductive performance of A. aeneociliella could improve integrated pest management programmes against this newly established species by disturbing its behaviour and reducing its reproduction potential. Based on ethological and reproductive biological approaches, the mating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Higher concentration (1 μg/μL) of female pheromone components did not affect the male response. Our previous observations showed that male behavioral responses were inhibited when presented with 3 females (Zhan et al, 2020), which may also be related to the higher concentration of female pheromone likely to be present. However, 1-nonanal (the male-produced pheromone) was only detected from treatments with males (1M1F and 2M), and this compound induced electrophysiological responses in the antennae of both males and females.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Higher concentration (1 μg/μL) of female pheromone components did not affect the male response. Our previous observations showed that male behavioral responses were inhibited when presented with 3 females (Zhan et al, 2020), which may also be related to the higher concentration of female pheromone likely to be present. However, 1-nonanal (the male-produced pheromone) was only detected from treatments with males (1M1F and 2M), and this compound induced electrophysiological responses in the antennae of both males and females.…”
Section: Discussionmentioning
confidence: 93%
“…3M : 1F) did not result in successful mating, even though it can induce male excitatory behavior (Zhan et al. , 2020). The ternary pheromone mixture may play a dual role in the regulation of sexual coordination in moths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that for specific-male, the less male-biased OSR (SC 1) caused more mating, eggs laid by all mated females per cage and thus higher percentage of eggs hatched per cage, while the more male-biased OSR (SC 2) only resulted in fewer mating and eggs laid by all mated females per cage (table 1). This may have been caused by a certain degree of male competition increasing the mating rate (Zhan et al ., 2020). However, the percentage of eggs hatched per cage decreased with the less female-biased OSR (SC 3) for specific females (table 1).…”
Section: Discussionmentioning
confidence: 99%